Immunopharmacology of platelets - Joseph, M. (Michel) (Handbook of immunopharmacology. Cells and mediators., 1995)
Platelets have long been the subject of much investigation in the areas of vascular physiology, biochemistry, immunology and physiopathology. Their ability to react to environmental stimuli, to modify their shape and metabolism despite being anuclear, has fascinated scientists. This volume looks specifically at the involvement of blood platelets outside their 'classical' field of application, in the physiopathological mechanics of allergy and inflammation. The coverage includes the role of platelets in bacterial, parasitic and viral diseases and in tumour cell interactions.